Implementation of Environment-Based Science Education to Enhance Environmental Awareness in High Schools - Fitriana, Allysha Syatifa; Harper, Evelyn; Richardson, Emily (Saba Jaya Publisher, 2025)
This research explores the implementation of Environment-Based Science Education (EBSE) to enhance environmental awareness in high schools. With mounting concerns over environmental degradation and increasing climate change, educating future generations about environmental issues and instilling a sense of responsibility towards the environment has become crucial. High schools serve as pivotal platforms for shaping students' attitudes towards the environment, making them ideal for EBSE implementation. The research methodology utilizes a narrative literature review approach, employing Google Scholar to identify relevant articles published between 2020 and 2024. Selection criteria include relevance to high school science education, a focus on environmental education, and its impact on environmental awareness. Findings indicate that EBSE is effective in improving environmental awareness, fostering environmental concern, enhancing academic performance, and scientific process skills. EBSE has been successfully integrated into high school science subjects. Further development of EBSE in high schools, including within science subjects and educational levels, is necessary. The use of innovative teaching methods and educational resources should be encouraged to cultivate environmental awareness from early childhood to adulthood. Integrating EBSE into the curriculum can empower students to proactively address environmental challenges.